Combined Use of Cognitive Behavioral Therapy (CBT) and Its Healing Impact on Drug Abusers Who Are Addicted to Drugs: A Scoping Review - Aeni, Nurul; Yosep, Iyus; Sriati, Aat (Faculty of Nursing, Universitas Hasanuddin, 2024)
Aims: The aim of this study is to assist individuals in healing from addiction; it is essential to implement a combination of interventions, such as CBT, that are proven to be effective in treating drug abuse with a holistic approach that integrates psychological and social aspects for optimal results, according to empirical evidence. Methods: The search databases for this study were PubMed, ScienceDirect, and Google Scholar. Identify articles published in the last 10 years (2014-2024), Randomized Control Trials (RCTs), English and Indonesian, Full-Text, and Teenagers to the Elderly. Using the PRISMA flowchart, data extraction and scoping with keywords (English):